Analisis Faktor Internal Dan Eksternal Yang Mempengaruhi Profitabilitas Bank Umum Syariah Di Indonesia Periode Triwulan Tahun 2012- 2018 - Moh Abdul Basir; Mulya E Siregar; Etty Puji Lestari (CV ODIS, 2021)
This study aims to analyze the effect of internal and external factors on the profitability of Islamic commercial banks in Indonesia during 2012-2018. The internal factors used in this study are derived from bank-specific factors such as capital adequacy ratio (CAR), efficiency ratio/operation costs on operating income (BOPO), financing to deposit ratio (FDR), and non-performing financing (NPF). The external factor used in this study such as interest rate, inflation, and Gross Domestic Product (GDP). The profitability of Sharia Comercial Banks proxied by Return on Assets (ROA). The Population of this study is 11 Sharia Commercial Banks that publish financial reports during the quarterly period 2012-2018. The novelty of this study such as, comprehensive study of Sharia Banking, using quarterly data, using macroeconomic factors which in previous studies were not discussed in-depth, and using panel data regression analysis. The result of this study indicates that CAR and GDP have a significant positive effect on ROA. Meanwhile, BOPO, FDR and NPF has significant negative effect on ROA